"Still Finding the Ground:" A Self-Study of a First-Year Physical Education Teacher Educator. Issue 1 (2nd January 2017) - Richards, K. Andrew R.; Ressler, James D.
Abstract: While decades of research have documented the socialization of inservice physical education teachers, the socialization of physical education faculty members has only recently become a research focus. Self-study of teacher education practices is becoming increasingly popular when exploring the lived experiences of physical education faculty. We used self-study of teacher education practices to understand the experiences of Kevin, a beginning physical education teacher educator in a visiting assistant professor position at Northern Illinois University. Kevin's experiences differ from those of many other teacher educators as he had not taught in school settings before moving into higher education. He did, however, have a strong background in higher education pedagogy through work in a center for teaching and learning. Data were collected through journaling, documents and artifacts, and exit slips, feedback forms, and focus group interviews completed by Kevin's students. Qualitative data analyses resulted in the construction of three first-order themes: (1) developing appropriate pedagogy, (2) developing and maintaining relationships with students, and (3) managing an identity as a teacher educator. Kevin's journey was non-linear and marked by both successes and challenges, but at the end of the year he felt that he had grown as a teacher educator. Further, while Kevin's youth and lack of teaching experience influenced his teacher education practice, it was not always negative and he found ways to compensate for what he lacked in direct teaching experience. Results are discussed with reference to Kevin's socialization and future directions for research are provided.